PONTOS CRÍTICOS DO PROCESSO DE PRODUÇÃO DE PISOS MACIÇOS DE MADEIRA - Philipe Ricardo Casemiro Soares; Marcos Milan; Ivaldo Pontes Jankowsky; Antonio Jose da Silva Maciel; Maria Raquel Kanieski (Ciência Florestal, 2012)
The quality concepts represent one of the important factors for the success of organizations and among these concepts the stabilization of the production process contributes to the improvement, waste reduction and increased competitiveness. Thus, this study aimed to evaluate the production process of solid wood flooring on its predictability and capacity, based on its critical points. Therefore, the research was divided into three stages. The first one was the process mapping of the company and the elaboration of flowcharts for the activities. The second one was the identification and the evaluation of the critical points using FMEA (Failure Mode and Effect Analysis) adapted methodology. The third one was the evaluation of the critical points applying the statistical process control and the determination of the process capability for the Cpk index. The results showed the existence of six processes, two of them are critical. In those two ones, fifteen points were considered critical and two of them, related with the dimension of the pieces and defects caused by sandpaper, were selected for evaluation. The productive process of the company is unstable and not capable to produce wood flooring according to the specifications and, therefore these specifications should be reevaluated.